PENGARUH DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN di PG. KREBET BARU MALANG - Nilawati Fiernaningsih; Pudji Herijanto (Adbis: Jurnal Administrasi dan Bisnis, 2019)
A successful company is a company that has employees in accordance with company needs, namely employees who have high work discipline who automatically have high productivity as well. This study aims to determine the effect of work discipline on work productivity of PG Krebet Baru Malang employees. The population of all employees of PG Krebet Baru Malang in the KB Installation Section II totaling 301 people. The analysis technique used is simple linear regression using the SPSS 24.0 application. The results of the study concluded that work discipline has an effect on work productivity.